Barriers to Capital Accumulation and the Incidence of Child Labor - Espinosa-Vega, Marco (IMF Working Papers; Working Paper, 2005)
The World Bank documents an inverse relationship between GDP per capita and child labor participation rates. We construct a life-cycle model with human and physical capital in which parents make a time allocation choice for their child. The model considers two features that have shown potential in explaining differences in states of development across nations. These are a minimum consumption requirement, and barriers to physical capital accumulation. We find the introduction of capital barriers alone is not enough to replicate the aforementioned observation by the World Bank. However, we find the interplay of a minimum consumption requirement and barriers to capital may enhance our understanding of child labor and the poverty of nations. Additionally, we find support for policies aimed at reducing capital barriers as a means to reduce child labor.